Critical Path Method and Gantt Chart-Based Truck Fleet Scheduling at PT. Bangun Jaya Sentosa - Fadhoilus Shofi; Diyan Agus Permana (Faculty of Islamic Economics and Business, Madura Islamic State University, 2026)
Purpose – This study aims to analyze and redesign truck operational scheduling at PT. Bangun Jaya Sentosa Pamekasan using the Critical Path Method (CPM) and Gantt Chart to identify critical activities, determine schedule flexibility, and reduce operational delays. Methodology – A descriptive quantitative case study approach was applied. Data were collected through process observation, interviews with the operational manager, scheduling staff, and drivers, and documentation of historical truck-rental records. Findings – The CPM analysis identified ten core activities with a critical path of A-B-C-D-E-G-H-J and a minimum operational cycle duration of 4,180 time units. Activities F and I were non-critical, with slack values of 360 and 320 time units. Implications – The findings extend scheduling theory by showing how criticality and slack can be interpreted jointly with fleet-management, queueing, and service-quality mechanisms in a demand-volatile local rental setting. Practically, the proposed schedule supports lower delay risk, reduced fleet idle time, more accurate truck-availability prediction, and stronger service reliability and responsiveness. Originality – The study converts deterministic CPM and Gantt Chart outputs into operational decision rules for urgent-order prioritization, service recovery, and vehicle-availability control under breakdown, rental-extension, and nighttime-access constraints.